Long-term nutrient management affects nitrogen dynamics and crop yield in rice (Oryza sativa)-wheat (Triticum aestivum) system - SHARMA, AJAY; DHERI, G S; SAINI, SAT PAL (The Indian Journal of Agricultural Sciences, 2021)
The present study was conducted to assess the in-season dynamics of nitrogen (N) in an Inceptisol under long-term fertilizer management in rice (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping system at Punjab Agricultural University, Ludhiana. The treatments comprised combination of chemical fertilizers (100% NPK and 150% NPK) and organic manures (100% NPK+FYM, 100% NPK+GM and 100% NPK+SI) along with unfertilized control laid out in randomized complete block design with three replications. Soil samples were collected at 30, 60, 90 and 120 days after transplanting/sowing and at harvest of rice and wheat, respectively and analysed for available N, ammonical N, nitrate N and total N. Plant samples were also collected at corresponding time period to determine the N content, uptake and biomass. Application of 100% NPK+FYM had significantly higher contents of different N forms during growth of both rice and wheat compared to rest of the treatments. At harvest of rice, combined use of 100% NPK and FYM improved soil available N and total N over 100% NPK by 20 and 22%; respectively. Whereas at wheat harvest; the increase in available and total N amounted to 29 and 23%, respectively due to corresponding treatments. The gradual decrease in N forms was observed till crop harvest. The grain and straw yield, content and total uptake of N by rice and wheat increased significantly under the integrated fertilizer management. Integrated nutrient management practice improved the relative proportion of plant-available N forms and achieved higher rice-wheat productivity.